HISTORY AND EVOLUTION OF ROLE LYRICS IN UZBEK POETRY (Scientific journal of the Fergana State University, 2023)
The article examines the stages of forming role-playing lyrics in Uzbek poetry, its history and evolution, the originality of the nature of the role lyrics. Using the example of the analysis of poems of the role-playing lyrics, Erkin Vokhidov shows the updates of forms and contents in modern Uzbek poetry.